Risk Factors for Cryptosporidiosis among Children in a Semi Urban Slum in Southern India: A Nested Case-Control Study - Sarkar, Rajiv (Am J Trop Med Hyg, 2014)
The risk factors for acquisition of cryptosporidial infection in resource-poor settings are poorly understood. A nested case-control study was conducted to assess factors associated with childhood cryptosporidiosis (detected by stool polymerase chain reaction) in an endemic, Indian slum community using data from two community-based studies with 580 children followed prospectively until their second birthday. Factors were assessed for overall cryptosporidiosis (N = 406), and for multiple (N = 208), asymptomatic (N = 243), and symptomatic (N = 163) infections, respectively. Presence of older siblings (odds ratio [OR] = 1.88, P = 0.002) and stunting at 6 months of age (OR = 1.74, P = 0.019) were important risk factors for childhood cryptosporidiosis. Always boiling drinking water before consumption, the use of a toilet by all members of the family, and maternal age ≥ 23 years were protective. These results provide insights into acquisition of childhood cryptosporidiosis in settings with poor environmental sanitation, contaminated public water supply systems, and close human–animal contact. Disease control strategies will require a multifaceted approach.